2004
DOI: 10.1179/026708304225012224
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evaluation of wear resistant high chromium, high carbon cast irons

Abstract: The microstructure of a series of experimental high chromium, high carbon cast irons was examined by optical and electron microscopy to determine the mechanisms that impart their resistance to wear by impact of reduced iron pellets at 550°C. The samples were cast following an experimental design in which the amount of different carbide forming elements was varied. The microstructure of these alloys was found to consist of a primary network of M 7 C 3 carbides surrounded by an austenitic matrix and eutectic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…These carbides were of the type M 7 C 3 , (M = Cr, Fe, V, Ti, etc.) but in less amount carbides of the types M 3 C, M 2 C, and MC were present and were surrounded by an austenitic matrix containing mainly Fe, together with Cr, SI, Mo, and Ni [16]. The change in the weight loss with time for the different specimens is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These carbides were of the type M 7 C 3 , (M = Cr, Fe, V, Ti, etc.) but in less amount carbides of the types M 3 C, M 2 C, and MC were present and were surrounded by an austenitic matrix containing mainly Fe, together with Cr, SI, Mo, and Ni [16]. The change in the weight loss with time for the different specimens is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 98%
“…Different specimens were prepared, with a chemical composition as shown in Table 1 following different considerations 2 International Journal of Corrosion to vary the microstructure of high chromium, high carbon castings as given elsewhere [16]. It was planned to maintain two levels of the ratio of the equivalent content of chromium (Cr E ) to the equivalent value of carbon (C E ) which were calculated from [17]:…”
Section: Methodsmentioning
confidence: 99%
“…In hypereutectic Fe-Cr-C coatings, M 7 C 3 carbides are present in the coatings as the main strengthening phase [8,9]. The excellent wear-resistance of the hypereutectic Fe-Cr-C coating is mainly attributed to the primary M 7 C 3 carbides [10,11]. However, as the primary M 7 C 3 carbides are usually coarse, the binding abilities of the M 7 C 3 carbides with the matrix are poor, and they can easily peel off of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that high chromium and carbon cast irons are extremely abrasion resistant owe to their carbide content and their orientation with respect to the wear surface played an important role in the wear behavior [16] [17]. A primary network of M 7 C 3 surrounded by an austenitic matrix and eutectic carbides, influenced on the wear mechanism in high C and Cr cast alloys [18]. Further, improved wear resistance has been reported if adding Mo, V and Ti, which in turn, has been related to the fine distribution of the eutectic aggregates [19].…”
Section: Introductionmentioning
confidence: 99%